Impact of Buccal Corridors on Smile Esthetics - Güvenç Başaran; İlknur Veli; Celal Genç; Törün Özer; Seher Gündüz-Arslan (Galenos Yayinevi, 2011)
Aim:The purpose of the present study was to investigate the influence of buccal corridors on smile esthetics.Subjects and Methods:For this purpose, 10 individuals with following criteria were included to this study; to have an esthetic smile arc, no excessive gingival exposure, ages between 18 and 30 years and equal distribution of the sexes. These criteria and only the perioral photographs were used to limit the scope of the variables and to decrease the dilution of the results. A photo editing software was used to produce 5 varying sizes of buccal corridors and the pictures were classified as Narrow smile, Medium-narrow smile, Medium smile, Medium-broad smile and Broad smile. Altered five smile images of the individuals were showed to the panels consisted of orthodontists, prosthodontists, general dentists, lay people and drawing artists each numbered 10 juries. They were asked to rate that five images from 1 to 5. ANOVA and Tukey tests were used to make a statistical analysis.Results:All of the panels evaluated the smile images in the same manner. The broader the smile it is the more attractive. The most attractive smile was the broad smile and the least attractive was the narrow smile. All panel groups evaluated the smile images in the same manner and there were not statistically significant differences between the groups. Conclusion:These results indicate that; to gain an esthetic smile after orthodontic treatment, clinician must avoid causing broad buccal corridors.